Impact of Leadership Styles on Job Performance; from Nurse’s Points of View at Benghazi Medical Centre - Eman Alaqeli; Ainas Altarhuni; Nidaal Almabrook (Khalij-Libya Journal of Dental and Medical Research, 2021)
Background and objectives. The relationship between leadership styles and job performance draws considerable attention from recent researchers. The main objective of this study was to determine the impact of leadership style (autocratic, democratic, and laissez-faire) on job performance from nurse’s points of view at Benghazi Medical Centre. Method. This study was a descriptive questionnaire-based study conducted on 100 nurses working at Benghazi Medical Centre, Libya. To analyze the data (mean, standard deviation, ANOVA test were used. Furthermore, multiple regressions and Pearson correlation were used to determine whether a relationship exists between the independent and dependent variables. Result. Of 100, only 60 questionnaires were completed, giving a response rate of 60%. The findings of this study indicated that democratic was the most dominantly used in the hospital, followed by the autocratic and laissez-faire leadership styles. Whereas, the laissez-faire leadership style had a strong positive and significant impact on performance (R2= .333; P < 0.01). Conclusion. Laissez-faire leadership style positively affected nurses’ performance. Future research that might be relevant to be further explored are worth.